2013
DOI: 10.1038/srep02564
|View full text |Cite
|
Sign up to set email alerts
|

Predicted spatio-temporal dynamics of radiocesium deposited onto forests following the Fukushima nuclear accident

Abstract: The majority of the area contaminated by the Fukushima Dai-ichi nuclear power plant accident is covered by forest. To facilitate effective countermeasure strategies to mitigate forest contamination, we simulated the spatio-temporal dynamics of radiocesium deposited into Japanese forest ecosystems in 2011 using a model that was developed after the Chernobyl accident in 1986. The simulation revealed that the radiocesium inventories in tree and soil surface organic layer components drop rapidly during the first t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
66
0
1

Year Published

2015
2015
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(68 citation statements)
references
References 25 publications
1
66
0
1
Order By: Relevance
“…Late in each of the simulation periods, the unmanaged aboveground biomass fluctuated due to self-thinning (Figure 2). As can be seen for 137 Cs in the RIFE simple compartment model (Hashimoto et al, 2013), our model also showed rapid migration of 137 Cs inventory from leaves to the forest floor (i.e., to litterfall and soil compartments), even though the migration via litterfall was represented as biomass-or C-based mass flow. This rapid migration was also comparable with field observations of Japanese cedar in Fukushima, where the 137 Cs inventory in the litter layer doubled from the autumn of 2011 to the autumn of 2012 (Kaneko et al, 2014).…”
Section: General Behavior Of Forothcs and A Sensitivity Test For The mentioning
confidence: 86%
“…Late in each of the simulation periods, the unmanaged aboveground biomass fluctuated due to self-thinning (Figure 2). As can be seen for 137 Cs in the RIFE simple compartment model (Hashimoto et al, 2013), our model also showed rapid migration of 137 Cs inventory from leaves to the forest floor (i.e., to litterfall and soil compartments), even though the migration via litterfall was represented as biomass-or C-based mass flow. This rapid migration was also comparable with field observations of Japanese cedar in Fukushima, where the 137 Cs inventory in the litter layer doubled from the autumn of 2011 to the autumn of 2012 (Kaneko et al, 2014).…”
Section: General Behavior Of Forothcs and A Sensitivity Test For The mentioning
confidence: 86%
“…Compared with European forests, the forests in Japan experience a warmer climate with higher mean annual precipitation. These differences make it likely that Japanese forests will circulate radiocesium deposited by the FNPP accident more rapidly than did the European forests following the Chernobyl accident (Hashimoto et al 2013 ). Indeed, the levels of radiocesium in trees dropped rapidly during the fi rst 2 years after the fallout, but radiocesium in the soil surface organic layer and soil surface layer (0-5 cm) components kept the same level during (Forestry Agency 2014.…”
Section: Infl Uence Of Diet On Radiocesium Concentrations In Freshwatmentioning
confidence: 99%
“…As the majority (~66%) of the landscape receiving high levels of radiocesium fallout (i.e. >1000 kBq m À2 ) were a mixture of evergreen and deciduous forests (Hashimoto et al, 2012), a significant quantity of radiocesium is also stored within the forest canopy, leaf litter, and soil organic matter (Hashimoto et al, 2013;Koarashi et al, 2012;Loffredo et al, 2014).…”
Section: Introductionmentioning
confidence: 99%